Goat and sheep production - Rajion, M.A. (Faculty of Veterinary Medicine and Animal Science, Universiti Pertanian Malaysia, 2016)
Goat and sheep production in Malaysia is mostly carried out by smallholders but there is a shift towards commercial production. There are presently about 288,500 heads of goats including the indigenous Kambing Kacang and about 235,000 heads of sheep including the indigenous Malin, various imported purebreds and crossbreds resulting from the mating between the imported and the indigenous breeds. Malaysia is only 9 percent self-sufficient in supplying the local mutton requirement and imports mostly in the form of frozen meat. The production systems practised for both species include tethering, extensive, intensive, semi-intensive and animal-tree crop integration systems, the latter being the most practical and widely practised by many government and private farms. Housing which is provided in all the production systems is normally of a raised type with slatted flooring. The local feed resources which support production include natural vegetation, several cultivated pastures except Brachiaria decumbens which is toxic and many agricultural byproducts of which palm kernel cake is by far the most widely used. The two most important diseases affecting goats and sheep are pneumonic pasteurellosis and haemonchosis. The major constraint which slow down production include the lack of land, feed resources and breeding stock, ineffective health programmes and poor marketing and promotion of mutton. Despite these problems, the goat and sheep industry has a bright future as indicated by the increasing trend in mutton production and consumption